Motor development in children 0‐2 years pre‐ and post‐LTX, a prospective study. (29th August 2020) - Bos, G. J. F. Joyce; Timmer, Carola Y.; Lelieveld, Otto T. H. M.; Scheenstra, Rene; Sauer, Pieter J. J.; Geertzen, Jan H. B.; Dijkstra, Pieter U.
Abstract: To determine prospectively gross and fine motor development of children <2 years of age, who undergo LTX. In this prospective study, children aged <2 years who undergo LTX were tested using the motor scale of the Bayley Scales of infant and toddler development, 3rd edition Dutch version. Testing was done during screening pre‐ and post‐LTX: at the time of hospital discharge (2‐6 weeks), at 3 months, 6 months, and 1 year. Z‐scores were calculated. Twenty‐nine children participated in this study, 14 boys, median age 6 months, at screening for LTX. Gross motor skills were delayed pre‐LTX (Z‐score −1.3). Fine motor skills were normal (Z‐score 0.3). Immediately post‐LTX, both skills reduced, and at 1 year post‐LTX, gross motor skills Z‐score was −1.0 and fine motor skills Z‐score 0.0. Both gross and fine motor skills Z‐scores decline post‐LTX and tend to recover after 1 year, gross motor skills to low normal and fine motor skills to normal levels. Monitoring of gross motor development and attention on stimulating gross motor development post‐LTX remains important, to enable participation in physical activity and sport for health benefits later in life.